Perspectives on the evolution of a fabrication laboratory in an emerging country: a comparative lexicometric study of European FabLabs. Issue 2 (22nd October 2021) - Ben Rejeb, Helmi; Roussel, Benoit
Abstract : Purpose: The purpose of this paper is to help in the establishment of the first fabrication laboratory (FabLab) in Tunisia. The FabLab movement offers many interesting opportunities through value creation, innovation, training and access to digital manufacturing technologies. A newly created FabLab should be well-positioned in terms of business model, purpose and management. The aim of this paper is to conduct a comparative analysis of FabLabs in developed countries (mainly in France and Luxembourg) and to provide recommendations on the possible development of a FabLab in Tunisia (FabLabENIT). Design/methodology/approach: Twelve FabLabs were visited and experts from the makers movement were interviewed. Data from the visits and interviews were analysed using lexicometric tools. This methodology is based on three main steps: first, the identification and selection of panel of studied FabLabs interviews; second transcribing and coding for IRaMuTeQ software; and third, correspondence analysis. Findings: The correspondence analysis determined five main factors of analysis that were interpreted using the most correlated words. The analysis of the correlation of the FabLabs and these five factors showed that FabLabENIT was strongly correlated with the third factor (interpreted as the organisation and structure factor). Recommendations for the purpose, local impact and methods were derived using the position of FabLabENIT in relation to the other factors. Practical implications: This study highlighted five main topics that characterise FabLabs in developing countries before and after their creation. A second practical contribution of this paper is that it provides a framework for FabLab managers and founders to anticipate possible trajectories of evolution for their organisations, especially in an emerging country. Another contribution, both practical and methodological, is the demonstration of the use of textual interview analysis tools (mainly correspondence analysis) to determine the main practices and characteristics of a creative organisation, such as a FabLab. Originality/value: One original feature of this paper is the topic of the study, especially in the current context of the COVID-19 outbreak, in which the FabLab movement provided interesting solutions that were designed and manufactured using digital manufacturing technologies. A second originality resides in the use of lexicometric techniques to analyse the information that was discussed during the interviews.